Association of dysglycemia with mortality in children receiving parenteral nutrition in pediatric intensive care unit - Khajavi, Leila; Khademi, Gholamreza; Mehramiz, Mehraneh; Norouzy, Abdolreza; Safarian, Mohammad (The Turkish Journal of Pediatrics, 2018)
One of the most important complications of parenteral nutrition (PN) is a high incidence of hyperglycemia. The aim of this study was to assess the effect of parenteral nutrition dysglycemia on clinical outcomes among critically ill children in pediatric intensive care unit (PICU). Charts of 201 critically ill children admitted in PICU during 2012-2015 were reviewed retrospectively. We included patients who were < 6 years of age and had received at least 60% of total energy from PN for a minimum of 5 days in PICU. The exclusion criteria were patients with diagnosis of diabetes mellitus, primary hypoglycemia, inborn errors of metabolism and patients who received dialyses. We defined hyperglycemia as blood glucose ≥150 mg/dl, and hypoglycemia as blood glucose ≤60 mg/dl. Based on blood glucose, patients were divided into four groups: `only hyperglycemia group` (having at least one hyperglycemia episode), `only hypoglycemia group` (having at least one hypoglycemia episode), `glucose variability` (having both hypoglycemia and hyperglycemia episodes), and `normoglycemia` (all glucose measurements were in normal range). Hyperglycemia and hypoglycemia occurred in 52.8% and 24.9% of all children, respectively; glucose variability occurred in 13.9% of all children. Multiple logistic regression analysis showed that glucose variability (OR: 3.1; 95% CI: 1.13-8.43) and hyperglycemia (OR: 2.14; 95% CI: 1.1-4.57) were associated with mortality independently. In `only hypoglycemia` group (N=22) there were only three deaths. There were no significant differences in the quantities of macronutrients prescribed via parenteral nutrition among the four blood glucose groups. Results of this study showed that hyperglycemia and glucose variability are strong predictors of mortality in pediatrics receiving parenteral nutrition.
Keywords: hyperglycemia; intensive care unit; parenteral nutrition; pediatrics